La elaboración de la información: Una aproximación teórica - Gómez-Ocaña, Concha (Teoría de la Educación. Revista Interuniversitaria, 2009)
In the article that we presented, we referred to the process of producing information at a biological level describing the characteristics of the brain, as we know about it’s existence and can justify it’s decisive role in the production of information we described the four principal flows of information, were it is demostrated stage by stage how the brain is shaped trough expierence. From this perspective we think that the function of intelligence is linked to part of the quantity and quality of the stimuli processed by the individual which he or she receives from the environment. Taking into account then, that the objective of education is to build the subject, refering naturally to the building of individual personality, and that such construction is carried out by actions which imply the modification of already existing structures and the appearance of new ones, at least in the functional sense, and that this activity is realised by the subject him or herself (levels of «ability» and formation); education acquires from this perspective a preponderant role. In the educational environment, one tries to achieve that the shaping of the individual is brought about by «activity of the individual provoked by educational action.